PENGARUH KONFLIK PARTISIPASI ANGGARAN TERHADAP KINERJA MANAJERIAL DENGAN KEPUASAN KERJA DAN KOMITMEN ORGANISASI SEBAGAI VARIABEL INTERVENING (STUDI EMPIRIS PADA PERUSAHAAN PERBANKAN DAN PEMBIAYAAN DI KOTA BENGKULU) - Sriwidharmanely, Sriwidharmanely; Usman, Darman; Devega, Lidya (JURNAL FAIRNESS, 2013)
This study aims to analyze the effect of budgetary participation conflict on managerial performance using job satisfaction and organizational commitment as intervening variables. The samples in this study consisted of 126 top level managers, middle level managers and lower level managers who participated in preparing the budgets. The data use analyzed using SEM (structural Equation Model). The results showed that the budgetary participation conflict has not negative significant effect on managerial performance, budgetary participation conflict has negative significant effect on job satisfaction, job satisfaction has not negative significant effect on managerial performance, budgetary participation conflict has negative significant effect on organizational commitment, organizational commitment has not positive significant effect on managerial performance, budgetary participation conflict through job satisfaction has not negative significant effect on managerial performance, budgetary participation conflict through the organizational commitment has negative significant effect on managerial performance.